Development and Performance Evaluation of Machine-Type Reciprocating Churner - Mashallah Ebrahimi; Farhad Khoshnam; Mohammad Reza Kamandar; Moslem Namjoo (Biomechanism and Bioenergy Research)
One of the old methods of butter production, which is still used in parts of Africa and the West of Asia, is the process of churning in the skin of a goat or deer that is half filled with milk or yogurt and air, which is beaten reciprocating. This type of butter production in the current research is mechanized and is called machine-type reciprocating butter churner (MRBC). This device is composed of chassis, churner, churn carrier, connector or crank, rotating wheel, driving system or power transmission and balance weights. In order to evaluate MRBC, the effect of churning amplitude (40, 60 and 80 cm), churning frequency (50, 61 and 72 cpm) and the churner volume (13.5 and 21.3 liters) on the butter yield was investigated. The results showed that the amplitude, frequency and churner volume had a significant effect on the butter yield at the level of 1%. Regardless of the churner volume, the minimum and maximum butter yield was obtained in the lowest and highest amplitude and frequency, respectively. The present study gives a general overview of the butter yield affected by machine mechanical parameters.